IMPROVING STUDENTS’ LITERACY READING SKILL USING E-BOOK SYSTEM ON THE TWELVETH GRADE AT SMA BOSOWA SCHOOL MAKASSAR - Cantika, Zhalsabila Putri; Batau, St. Haliah; Muliati, Muliati (Lembaga Jurnal FKIP Universitas Bosowa, 2023)
This study aimed to determine to improve students’ Literacy Reading skill Using E-Book System of twelveth grade students of SMA Bosowa School Makassar. This study used a pre-experimental method. The Subject of this study were students of twelveth grade SMA Bosowa School Makassar semester in the academic year 2023/2024, with a sample of 10 students. Data collection was reading text using E-Book System. The research data collected through the test showed that the student's reading ability after the research was conducted, students were more interested in using the E-Book System in reading English text. Based on the results of the data analysis, it can be seen that the student's results in the pre-test were 64.00. Then after getting treatment, the students' pre-test scores increased to 85.55 in the post-test. It can be concluded that students' reading skills are improved on the students’. So it can be concluded that using the E-Book System can improve students' learning ability in reading English texts at SMA Bosowa School Makassar